Julio Tello as a medical anthropologist: assessing the antiquity of syphilis in ancient Peru - Christian Mesía-Montenegro (História, Ciências, Saúde: Manguinhos)
Abstract This paper explores the methods used by Julio Tello to address the antiquity of syphilis in ancient Peru, examining his thesis La antigüedad de la sífilis en el antiguo Perú to understand the logic behind the procedures he used to test his hypothesis. The contention presented here is that despite being a medical thesis, his text can actually be considered an exploration of the origins of syphilis using a truly anthropological method, making Tello a pioneer in the subfield of medical anthropology in the Andes.